Analysis of Seepage Control Effect of Gate Foundation Cut-off Wall Based on Finite Element Method - LIU Jian; FU Chenghua; WANG Xinghua; MU Xiaoxiao; LIU Qingbin (Renmin Zhujiang)
The seepage of gate dam foundation has become one of the important issues caused by theaging of dam foundation seepage control facilities. When the seepage flow endangers the safety ofgate foundation, it is very difficult to carry out the late anti-seepage treatment ofgate foundation, so the setting and effects of seepage control facilities should be fullyconsidered in the design stage.Taking Zhaohua Power Station in Guangyuan, Sichuan as anexample,this paper establishes the seepage calculation model of gate foundation by finite elementmethod, calculates and analyzes the change law of seepage flow and seepage slope of the gatefoundation when the depth and thickness of the cut-off wall before the gate foundation change,and evaluates the seepage control effect of the cut-off wall with different sizes. The analysisresults can provide reference for the design of seepage control measures for gate foundation andthe selection of seepage control measures for similar gate foundation.